ESOPHAGEAL LEIOMYOSARCOMA - E. N. Novozhilova; V. I. Popadyuk; P. V. Kononets; D. Yu. Kanner; A. I. Chernolev; E. M. Marksitser; O. V. Olyshanskaya (Сибирский онкологический журнал)
In 2017, esophageal cancer was detected in 7126 patients, including 1962 patients with cervical esophageal cancer. Metastases in regional lymph nodes were detected in 60–70 % of cases. the 5-year survival rate was 25–50 %. Currently, the benefits of minimally invasive surgeries for cancer have been proven, but these surgeries have restricted indications leiomyosarcoma is a rare malignant tumor of smooth muscle, accounting for about 0.3 % of the malignant tumors of the esophagus. Case presentation. in our first clinical case, we have shown the feasibility of performing surgical resection of cervical esophageal carcinoma with larynx preservation. We have described a rare postoperative complication bending of the graft. the complication was resolved and good voice, protective and swallowing functions were achieved. in the second case, the tumor initially spread to the pear-shaped sinus and beyond the cricoid area, which was a contraindication for the organ-preserving surgery. Conclusion. the extent of surgery should always be planned taking into account the extension of the primary tumor. in our practice, we prefer to use visceral (intestinal) transplants for patients with circular pharyngeal defects, thus allowing radical surgery to be performed and esophageal motility to be restored. this technique helps patients recover faster after surgery.